Advances in Information Technology Third International Conference, IAIT 2009, Bangkok, Thailand, December 1-5, 2009. Proceedings - Papasratorn, Borworn.; Chutimaskul, Wichian.; Porkaew, Kriengkrai.; Vanijja, Vajirasak. (Communications in Computer and Information Science, 2009)
This book constitutes the proceedings of the Third International Conference on Advances in Information Technology, IAIT 2009, held in Bangkok, Thailand in December 2009. The volume aims to provide a forum for researchers, educators, government officers,consultants, private sectors, managers, developers and others in the rapidly growing field of information technology to meet, discuss and exchange ideas on recent advances.